Carbon nanotubes field-effect transistor pressure sensor based on three-dimensional conformal force-sensitive gate modulation. (February 2023) - Cheng, Guanyin; Xu, Haitao; Gao, Ningfei; Zhang, Mengqin; Gao, Hailin; Sun, Bihao; Gu, Mingxin; Yu, Leyong; Lin, Yuanchang; Liu, Xueqin; He, Guotian; Wei, Dapeng
Abstract: Pressure sensors based on field-effect transistor mechanism has received a lot of attention from researchers, which can effectively suppress low contrast and crosstalk effects. In this paper, we demonstrate a pressure sensor based on carbon nanotube field-effect transistor (CNTs-FET) and three-dimensional conformal force-sensitive top electrode with high sensitivity and easy integration. The high mobility field-effect transistor sensors were prepared using CNTs films with 99.9999% semiconductor concentration as the channel material. Conformal graphene nanowalls (GNWs) film on pyramidal micro-structure arrays worked as force-sensitive top electrode, the field-effect transistor sensor shows a sensitivity of 946.23 kPa −1 and 43.79 kPa −1 in the linear range of 0–30 Pa and 0.03–10 kPa, much higher than piezoresistive sensor (the sensitivity of about 377.73 kPa −1 ) and capacitive sensor (the sensitivity of 115.78 kPa −1 ). And the sensitivity and range of the sensor can be adjusted by the force-sensitive layer orientation design. Additionally, the sensor's response time is less than 30 ms, the recovery time is about 30 ms. The field-effect pressure sensor could detect ultra-low pressure (about 1.3 mg) of the chrysanthemum petals, and also could record the dynamic crawling process of the insect. Graphical abstract: Image 1